Optimization of biomass-fueled vertical corn drying: Efficiency, energy balance, and sustainability - Sukmawaty Sukmawaty; Syahrul Syahrul; Amuddin Amuddin; Sri Helmayana Rahmi; Ahmad Ibrahim Syahrul (Results in Engineering)
This study investigates the thermal performance and energy efficiency of a biomass-fueled vertical dryer utilizing candlenut shell biomass for corn drying. The objective is to evaluate drying behavior under continuous and discontinuous operation modes at different temperature settings. A custom-built dryer was developed and tested at 45 °C, 50 °C, and 55 °C, and energy input, drying time, and efficiency were recorded. Statistical analyses, including paired t-tests, were conducted to examine the significance of operational differences. Results show that continuous drying at 50 °C and 55 °C significantly improves drying efficiency, reaching above 66 %, and reduces drying time compared to discontinuous modes. Candlenut shells performed well as a renewable fuel, offering stable combustion and minimal ash production, outperforming traditional fuels such as rice husks and corn cobs in similar drying conditions. Energy analyses indicated balanced energy use, while future work should address post-drying quality characteristics and automation. These findings suggest that candlenut shells are a viable, sustainable alternative for efficient post-harvest thermal processing, particularly in rural agro-industrial settings.